2002
DOI: 10.1016/s0022-5347(05)64560-0
|View full text |Cite
|
Sign up to set email alerts
|

Serum Testosterone Suppression and Potential for Agonistic Stimulation During Chronic Treatment With Monthly and 3-month Depot Formulations of Leuprolide Acetate for Advanced Prostate Cancer

Abstract: We conclude that monthly and 3-month sustained release (depot) formulations of leuprolide acetate provide consistent, uniform suppression of serum testosterone throughout the respective dosing intervals, and that the initial depot injection of each formulation provides sufficient pituitary desensitization to prevent agnostic stimulation of serum testosterone during chronic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 8 publications
1
23
0
2
Order By: Relevance
“…Furthermore, endometrial atrophy was detected in 65.8%, and amenorrhea in 90%. These findings support the biological capacity of goserlin acetate, a testosterone derivative, to reverse endometrial growth [23].In the current study, it is found that an increased in Test levels in G2, due to the potential occurrence of testosterone surges on repeat injection of the goserelin acetate has also been investigated by [24].Conversely, the highly significant decrease of estrogen in G2 compared with G1. Goserelinacetateis medicines that work by causing a temporary menopause.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, endometrial atrophy was detected in 65.8%, and amenorrhea in 90%. These findings support the biological capacity of goserlin acetate, a testosterone derivative, to reverse endometrial growth [23].In the current study, it is found that an increased in Test levels in G2, due to the potential occurrence of testosterone surges on repeat injection of the goserelin acetate has also been investigated by [24].Conversely, the highly significant decrease of estrogen in G2 compared with G1. Goserelinacetateis medicines that work by causing a temporary menopause.…”
Section: Discussionsupporting
confidence: 82%
“…It has been suggested that this 'biochemical flare', occurring in 4-63% of patients, could cause clinical 'flares of disease', with reports of increased pain from bone metastases, spinal cord compression, pathological fractures, bladder outlet obstruction, and even death (Bubley 2001, Heidenreich et al 2011. Besides the initial flare, miniflares are observed within 12 h after the second or subsequent administration of the LHRH agonist , Sharifi & Browneller 2002. To prevent these flares, antiandrogens (see below) are being combined with LHRH agonistic treatment, before and during the first weeks, to reach a total androgen blockade.…”
Section: Figurementioning
confidence: 99%
“…The C max values of the one-month and threemonth depot injections based on PLGA depot formulations of leuprolide were observed to be 10.7 and 20.8 ng/ml in clinical practice [40]. Although the C max values of these two formulations were significantly different, they showed the same flare-up and complete downregulation of testosterone to the castration range (≤ 0.5 ng/ml for testosterone) [40,41]. Moreover, Viadur ® , a leuprolide implant, was…”
Section: Pharmacokinetic and Pharmacodynamic Studiesmentioning
confidence: 99%